2019
DOI: 10.3390/children6040059
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Ergonomic Challenges of Ventilating a Premature Infant During Delayed Cord Clamping

Abstract: Delayed cord clamping (DCC) is endorsed by multiple professional organizations for both term and preterm infants. In preterm infants, DCC has been shown to reduce intraventricular hemorrhage, lower incidence of necrotizing enterocolitis, and reduce the need for transfusions. Furthermore, in preterm animal models, ventilation during DCC leads to improved hemodynamics. While providing ventilation and continuous positive airway pressure (CPAP) during DCC may benefit infants, the logistics of performing such a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…15 Clinical trials have shown that delayed cord clamping reduces the incidence of necrotizing enterocolitis by preventing hypovolemia. 35,36 In the present study, none of the preterm infants developed necrotizing enterocolitis, and there was no difference in the incidence of feeding intolerance between the DCC group and the ECC group.…”
mentioning
confidence: 37%
“…15 Clinical trials have shown that delayed cord clamping reduces the incidence of necrotizing enterocolitis by preventing hypovolemia. 35,36 In the present study, none of the preterm infants developed necrotizing enterocolitis, and there was no difference in the incidence of feeding intolerance between the DCC group and the ECC group.…”
mentioning
confidence: 37%
“…However, feedback from involved personnel in our study revealed that behind the seemingly simple intervention of moving equipment and personnel to the potentially compromised infant, lay several logistic challenges, as well as communication and collaboration issues. These issues have also been encountered by other researchers [29,37,43,44]. Examples include: ensuring availability and readiness of the equipment with several deliveries going on at the same time, collaboration and planning ahead in rapidly progressing deliveries, and how to manage space constraints at the birthing bed.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are consistent with the study done by Ibrahim et al ( 11 ) where the majority of respondents agreed that DCC is beneficial for both term (69%) and preterm (71%) neonates not requiring PPV. In fact, DCC in preterm neonates who require PPV can now be facilitated by providing a mobile resuscitation trolley before UCC ( 21 ) and this was proven to be feasible as demonstrated by Lapcharoensap et al ( 22 ) and Joshi et al ( 23 ). Having said that, only 30% of the respondents agreed that DCC was good for neonates who require PPV.…”
Section: Discussionmentioning
confidence: 99%